VALIDITY OF GRAYSCALE ULTRASOUND AND RESISTIVE INDEX IN THE DETECTION OF NATURE OF OVARIAN NEOPLASMS BY TAKING HISTOPATHOLOGY AS A GOLD STANDARD - Akram, Faiza; Ali, Azmat; Kiani, Sumaira; Asma, Bibi; Bibi, Saima; Zafar, Danish (Journal of Ayub Medical College Abbottabad, 2020)
Background: The utility of ultrasound has long been established in the diagnosis of benign and malignant ovarian neoplasms. Ultrasound is a safe and non-invasive imaging modality that has a high sensitivity and specificity. The objective was to determine the validity of grayscale ultrasound and resistive index in the detection of nature of ovarian neoplasms by taking histopathology as a gold standard. Methods: It was Cross-sectional study conducted in department of Radiology, Ayub Teaching Hospital Abbottabad from May 16 to November 30, 2014. Two-hundred-twenty-one female patients in whom an adnexal mass was noted on pelvic ultrasound were included in the study. Results: Out of these 221 patients, malignant ovarian masses were present in 50 (22.62%) patients on grayscale ultrasound. While a resistive index ‰¤0.6 was found in 56 (25.34%) patients. Over all the sensitivity of grayscale ultrasound was 95% and the specificity was 93.37%. Likewise, the sensitivity and specificity of resistive index were 95% and 90.06% respectively. Conclusion: This study showed the grayscale ultrasound is a sensitive imaging modality for differentiation of benign and malignant ovarian masses. Keywords: Adnexal masses; Ultrasound; Doppler; Resistive Index; Carcinoma; Ovary